Does the Addition of Either a Lateral or Posterior Interbody Device to Posterior Instrumented Lumbar Fusion Decrease Cost Over a 6-Year Period?. Issue 5 (August 2018) - Schadler, Paul; Derman, Peter; Lee, Lily; Do, Huong; Girardi, Federico P.; Cammisa, Frank P.; Sama, Andrew A.; Shue, Jennifer; Koutsoumbelis, Stelios; Hughes, Alexander P.
Study Design: Retrospective case-control study. Objectives: Few studies have compared the costs of single-level (1) posterior instrumented fusion alone (PSF), (2) posterior interbody fusion with PSF (PLIF), and (3) lateral interbody fusion with PSF (circumferential LLIF). The purpose of this study was to compare costs associated with these procedures. Methods: Charts were reviewed and patients followed-up with a telephone questionnaire. Medicare reimbursement data was used for cost estimation from the payer's perspective. Multivariate survival analysis was performed to assess time to elevated resource use (greater than 90% of study patients or $68 672). Results: A total of 337 patients (PSF, 45; PLIF, 222; circumferential LLIF, 70) were included (63% follow-up at 6 years). PSF and circumferential LLIF patients were 3 times more likely to reach the cutoff value compared with PLIF patients ( P = .017). Conclusions: Circumferential LLIF and PSF patients were more likely to have higher resource use than PLIF patients and thus incur greater costs at 6-year follow-up.